Calculating the average natural recharge in large areas as a factor of their lithology and precipitation - Sanz, E.; Menéndez Pidal de Navascués, I.; Távara, C. (2018)
In an area as large as Spain, it is shown by statistical inference on a sample of 875 springs (with discharges greater than 10 l s −1 ), whose average flow, lithology and catchment areas are known, and which were grouped into regions of contrasting rainfall, that the average annual recharge is a fixed fraction of annual rainfall for each lithology. Recharge rates have thus been established with respect to rainfall for six lithological groups of different permeability: sands, gravels and generally alluvial formations 8.3%; conglomerates, 5.6%; sandstones, 7.3%; limestone and dolomite 34.3%; marls, marly limestones, silts and clays, 3.3%; and hard rocks, 1.3%. Since Spain can be considered to be representative, given its large size and a highly varied lithology, topography and rainfall, these recharge rates with respect to rainfall are probably quasi-universal values, which can be used to estimate the average recharge or average groundwater resources of large regions in any part of the world (except in special cases such as areas that have permafrost). In any case, the recharge rates can be adapted for each region according to its particular characteristics. Rainfall and lithology data are abundant, and so the method can be widely used to calculate hydraulic balances. The method has been applied to the Duero basin in Spain and to other European countries (Portugal, Ireland and Italy), obtaining recharge results that are very similar to those calculated by other methods.